Study on the impact of green finance on green total factor productivity in forestry—evidence from China - Gong, Hao; Wang, Zhenhong (Frontiers in Environmental Science, 2024)
China's forestry industry's ecological, economic, and social benefits have improved significantly.However, practical problems remain, such as irrational industrial structure, serious resource consumption, and low environmental transformation efficiency. Green total factor productivity is an important index to measure the transformation of economic development mode, and improving green total factor productivity in forestry is of great significance in guiding the transformation of forestry economy, improving the structure of agricultural economy, and realizing the green development of forestry economy. Based on the panel data of 30 provinces and cities in China from 2006 to 2021, the article adopts the entropy value method and the GML index based on the SBM directional distance function to construct the index system of green finance and forestry green total factor productivity and empirically analyzes the impact and mechanism of green finance on forestry green total factor productivity. It was found that (1) green finance can improve local forestry green total factor productivity and influence the neighboring regions to improve forestry green total factor productivity through economic spillover effect, and the coefficient of spatial spillover effect was 0.1041. (2) there were regional differences in the impact of green finance on forestry green total factor productivity, which was explicitly presented as a gradual decrease from east to west. ladder-like". (3) There was a 30.46% intermediary effect of forestry industry structure in the influence of green finance on forestry green total factor productivity. (4) There was a double-threshold effect of human capital in the influence of green finance on forestry green total factor productivity, and there was a non-linear effect of marginal increment in the influence of green finance on forestry green total factor productivity after the threshold of 5.87 human capital. Based on China's ecological and economic development background, it was significant to utilize green finance to solve forestry economic development problems and promote China's green and sustainable development; therefore, put forward policy recommendations.